Phytochemical Profile and Anticancer Potential of Helichrysum arenarium Extracts on Glioblastoma, Bladder Cancer, and Breast Cancer Cells - Ihsan Nalkiran; Hatice Sevim Nalkiran (Pharmaceuticals)
Background/Objectives: Cancer is the second leading cause of death globally. Medicinal plants have emerged as fundamental sources of bioactive compounds with anticancer potential, largely attributed to their diverse secondary metabolites. This study aimed to investigate the cytotoxic effects of Helichrysum arenarium extracts from two distinct regions of Turkiye, Mersin, and Artvin, on cancerous (MDA-MB-231, RT4, T98G) and non-cancerous (ARPE-19, hGF) cell lines and to identify bioactive compounds responsible for these effects. Methods: H. arenarium plant extracts were prepared using ethanol and methanol as solvents, followed by lyophilization and dissolution in DMSO. The cytotoxic effects of the extracts were evaluated using Hoechst staining and MTS assays to assess cell viability. IC50 values and selectivity indices were calculated. Phytochemical composition was analyzed using Quadrupole Time-of-Flight mass spectrometry. Results: The ethanol extract from Mersin (HAE-M) demonstrated superior cytotoxicity, particularly against breast and bladder cancer cells, while showing minimal impact on non-cancerous cells. HAM-M, HAE-A, and HAM-A exhibited comparatively less potent effects. Phytochemical analysis of HAE-M identified 16 bioactive compounds, including Naringenin, Luteolin, and Quercitrin, known for their antioxidant and anticancer properties. Conclusions: These findings highlight the potential of H. arenarium extracts, particularly HAE-M, as a source of potent anticancer agents. This study is novel in its comprehensive analysis of different extraction methods and regional plant sources, combined with phytochemical profiling, to identify selective anticancer effects. Further investigations into the mechanisms of action of these extracts could contribute to the development of plant-derived anticancer therapies.